Orthodontic treatment induces Th17/Treg cells to regulate tooth movement in rats with periodontitis - Nan Ge; Jing Peng; Lan Yu; Shuo Huang; Lu Xu; Ying Su; Li Chen (Iranian Journal of Basic Medical Sciences, 2020)
Objective(s): Here we investigated the regulation of Th17 and Treg cells in orthodontic tooth movement during periodontal inflammation. Materials and Methods: Fifty-six SD rats were divided into a control (24 rats) and a tooth movement group during the recovery stage of periodontitis (RM group, 32 rats). Periodontitis was established by silk ligation and local injection of LPS. Orthodontic tooth movement was achieved by nickel-titanium springs on the maxillary first molars. The proportions of Th17 cells and Treg cells were evaluated by flow cytometry. Gene expression of ROR-γt and Foxp3 was determined by real-time PCR. Expression of ROR-γt, Foxp3, RANK, RANKL, and OPG was detected by immunohistochemical staining. Osteoclasts were detected by TRAP staining. Relationships between Th17/Treg cells, osteoclasts, and related factors were estimated by correlation and regression analysis. Results: During orthodontic tooth movement in the recovery stage of periodontitis, the proportion of Th17 cells, ROR-γt, RANK, osteoclasts, and the RANKL/OPG ratio increased and then decreased. The proportion of Treg cells and Foxp3 increased, then decreased, and increased again. Levels of RANKL and OPG increased, then decreased, then increased, and finally decreased. The Th17/Treg ratio initially decreased, then increased, and decreased again. Th17 cells were positively correlated with RANK and RANKL, the RANKL/OPG ratio, and counts of osteoclasts. Treg cells were negatively correlated with RANK expression and numbers of osteoclasts. The Th17/Treg ratio was positively correlated with RANK expression and numbers of osteoclasts. Conclusion: Under periodontal inflammation conditions, the Th17/Treg ratio might regulate orthodontic tooth movement through changing osteoclasts metabolism.